Pengaruh Pelayanan Terhadap Kepuasan Pelanggan dan Implikasinya Terhadap Citra Perusahaan Studi Kasus Pada Hotel Mirah Bogor - Maulana, Miki; Mulyana, Mumuh (LPPM Institut Bisnis dan Informatika Kesatuan, 2013)
Service is a kind of direct and indirect communication from the producen to the costumer to measure how for the customer to buy and consume, if they can have satisfaction to the product that they will trust and keep using our product. The main target of this research is the identification how good is the service that give by MIRAH HOTEL Bogor, how big is the customer satisfaction MIRAH HOTEL Bogor.The method of analysis is quantitative method with regretion and correlation formula, to answer of question, when questioner used and draft to respondent. The Implication to image of the company a djuge from how the service and facilities inside MIRAH HOTEL bogor, customer satisfaction and its implications for corporate image in question. services have a significant effect on perceived ease of customer satisfaction with a coefficient of 0,46. It can be proved by looking at the value of t statistics of 6,26 greater than 1,96. PLS results indicate that the construct of service quality has a positive effect on customer satisfaction This means that the first hypothesis is accepted, the proven quality of service effect customer satisfaction. Quality of service that increases customer satisfaction causes more significant effect on perceived ease of customer satisfaction with the coefficient of 0,46. It can be proved by looking at the value of t statistics for 11,90 of greater than 1,96. While the second hypothesis customer satisfaction has a positive effect on corporate image study was to prove the second hypothesis is accepted, customer satisfaction is proven to effect the company's image. Keywords : Service, Customer Satisfaction, Brand Image